2021
DOI: 10.3389/fphys.2021.629674
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Blood Flow Acutely Increases Endothelial Microparticles and Decreases Flow Mediated Dilation in Patients With Heart Failure With Reduced Ejection Fraction

Abstract: IntroductionDisturbed blood flow, characterized by high retrograde and oscillatory shear rate (SR), is associated with a proatherogenic phenotype. The impact of disturbed blood flow in patients with heart failure with reduced ejection fraction (HFrEF) remains unknown. We tested the hypothesis that acute elevation to retrograde and oscillatory SR provoked by local circulatory occlusion would increase endothelial microparticles (EMPs) and decrease brachial artery flow-mediated dilation (FMD) in patients with HFr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Low shear rate (SR) reduces NO bioavailability by decreasing eNOS expression, thereby exposing the endothelium to the atherogenic effect of risk factors. In humans, it has been consistently shown that acute elevations to retrograde and oscillatory SR decrease the FMD of atherosclerosis-prone and resistant conduct arteries ( Thijssen et al, 2009 ; Schreuder et al, 2014 ; Silva et al, 2021 ). However, the interactive effect of blood flow disturbances and PPL on endothelial function is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low shear rate (SR) reduces NO bioavailability by decreasing eNOS expression, thereby exposing the endothelium to the atherogenic effect of risk factors. In humans, it has been consistently shown that acute elevations to retrograde and oscillatory SR decrease the FMD of atherosclerosis-prone and resistant conduct arteries ( Thijssen et al, 2009 ; Schreuder et al, 2014 ; Silva et al, 2021 ). However, the interactive effect of blood flow disturbances and PPL on endothelial function is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence showed that a single high-fat meal produced a significant increase of EMV plasma levels in healthy normolipidemic individuals ( Ferreira et al, 2004 ; Tushuizen et al, 2006 ). Also, acute elevations in retrograde and oscillatory SR on the brachial artery increases EMV levels in the circulation of healthy subjects ( Whittaker and Przyklenk, n.d. ; Jenkins et al, 2013 ) and patients with risk factors ( Rocha et al, 2018 ) and cardiovascular disease ( Silva et al, 2021 ). However, whether the combination of PPL and DBF exacerbate the increase in EMV levels is also unknown.…”
Section: Introductionmentioning
confidence: 99%